An Academic Study on Impact of the Turkish Drama "Kurulus Osman" on the Culture of the Indian Subcontinent in the Context of Historical Dramas - DR. MUHSİN RAMAZAN İŞSEVER; ZEYNEP ALTINKÖPRÜ (دریافت)
Television and other mass media play a significant role in history education. Visual and auditory content makes historical events more comprehensible, while educational programs, documentaries, films, and series provide in-depth information. In this context, the United States has been successful in transmitting its cultural history to different nations through popular culture sources. While educational programs offer systematic knowledge, documentaries provide detailed information by covering real events and people. Cinema uses dramatic storytelling techniques to bring historical events to a broad audience and help viewers form an emotional connection. Series, on the other hand, offer a detailed and comprehensive narrative by addressing historical events and figures from a broader perspective. This study examines the impact of the Turkish series “Kurulus Osman” on the culture of the Indian subcontinent. “Kurulus Osman” provides viewers with a historical perspective by dramatically portraying the founding period of the Ottoman Empire. The reception of the series in the Indian subcontinent, its audience, and popularity on social media have been researched. Additionally, the series' impact on Indian culture, including whether it has increased interest in historical events, has been analyzed with statistical data. The series' effects have been assessed within the framework of media and cultural impact theories, and academic sources have been cited on the role of cultural transmission in history education. The importance of the series in terms of history education and cultural interaction has been highlighted.